A Comparative Study of Academic Performance of Teachers Among Self-Financing Colleges and Government and Aided Colleges - Tyagi, Rica (Journal of Commerce and Trade, 2013)
The present study is an humble attempt in this direction. Thus, the present study attempts to make a comparative study of academic performance of the teachers teaching traditional courses in self-financing colleges and that of the teachers teaching the same courses in Govt. & aided colleges of C.C.S. University, Meerut. The only objective of the paper is to make a comparative study of academic performance of the teachers teaching traditional courses in self-financing colleges and that of the teachers teaching the same courses in Govt. & aided colleges. From the foregoing analysis it can safely be concluded that whether they are girls colleges or co-ed colleges or they are combined together we find that academic performance of the teachers teaching Arts subjects in self-financing colleges and that of the teachers teaching the same subjects in Govt. & aided colleges is almost equal. To be more clear, teachers teaching in self-financing colleges are performing at par with the teachers teaching in Govt. & aided colleges.